Anxiolytic and Antidepressant Effect of Phaseolus vulgaris on Animal Models - Rabia Munawwar; Sana Sarfaraz; Rahila Ikram; Talat Zehra; Humaira Anser; Huma Ali (Scientifica)
An experimental study was conducted using rodents at different doses to evaluate the effect of Phaseolus vulgaris (red beans) on cage crossing, head dip, open field, elevated plus maze, and light and dark apparatus for anxiety and forced swim test for depression. The corticosterone level and histopathological evaluation was also done to correlate the antidepressive impact of the red beans. The study also identified the components responsible for the effect using GCMS. Based on the findings, red beans could be a potential non-pharmacological therapy for mild to moderate depressive patients. The anxiety model was conducted on mice weighing 20–25 gms. Group I was taken as control, group II as 500 mg/kg and group III as administered 1000 mg/kg. The tests were performed on 0th, 7th, 15th, 30th, 45th, and 60th day. The depression model research was conducted on albino rats weighing between 180 and 200 g, divided into four groups: a control group, a 500 mg/kg Phaseolus vulgaris group, a 1000 mg/kg Phaseolus vulgaris group, and a standard group treated with fluoxetine. The forced swimming test was performed on days 0, 7, 15, 30, 45, and 60, after which histopathological evaluations were conducted and blood samples were taken to assess corticosterone levels. GCMS was used to identify the constituents present in red beans, while optical spectroscopy was used to detect minerals and ions. Results showed that both doses of Phaseolus vulgaris possess anxiolytic effect and increased the struggling time of rats in depression model significantly, with the 1000 mg/kg dose showing more significant results than the 500 mg/kg dose. The GCMS results identified the presence of erucic acid, which causes an increase in α-amylase, thus reducing depression. Optical spectroscopy also showed that red beans contain zinc, which may increase BDNF and help in treating depression.